Corporeality and creativity, between tradition and innovation - Didier, John (Swiss Journal of Educational Research, 2018)
Craft disciplines are traditionally associated with the transmission of technical gestures in a school setting. Since they became, within the context of compulsory education and despite themselves, the ambassadors for creativity, these technical disciplines embedded in manual representations, leads us to rethink the teaching technical gestures and the knowledge to be taught to students. By introducing design approaches within the acting of the creative and manual activities teacher, we reinstate the issue of corporeality, of knowledge and body techniques in line with nowadays social practices. Also, fostering the development of creativity as an ability to produce innovative and tailored ideas refers to teaching complex tasks such as problem solving.